Islam Nusantara: Relasi Islam dan Budaya Lokal - Luthfi, Khabibi Muhammad (SHAHIH : Journal of Islamicate Multidisciplinary, 2016)
AbstractThe objective of this article is to explore the concept of Islam Nusantara (IN) observed from the structural theory of Islam and local culture relation, along with the reason why IN is developed into the concept of the Islamic proselytizing Rahmatan lilâalamin by the intellectual Nahdhatul Ulama (NU). It comes from the NU Intellectualâs claim that IN is the mediator in the controversy of Islam and local culture relation, moreover in the global scale it is going to be proselytized in the International, whereas the IN is still regarded as an issue and has not fulfilled the knowledge standard yet.Â  Through philosophical approach, socio-anthropolinguistics based on the data in www.nu.or.id and topic analysis as its data analysis, it is found that the intellectual of NU used eight approaches to concept the IN. The IN set that Islam influences Indonesian culture and the INâs success and ability to dialogue with Indonesian culture trigger the intellectual NU to promote it to the International.Â Keywords:Â  Islam, Nusantara, culture, Indonesia, ValueÂ Â AbstrakTujuan tulisan ini adalah mengkaji konsep Islam Nusantara ditinjau dari struktur teori relasi Islam dan budaya lokal serta alasannya dijadikan sebagai konsep dakwah Islam rahmatan lil âalamiin oleh intelektual NU. Ini berangkat dari âclaimâ intelektual NU bahwa konsep ini adalah penengah dalam perdebatan relasi Islam dan budaya lokal, bahkan dalam skala global ingin didakwahkan di dunia Internasional. Padahal Islam Nusantara baru sebatas wacana yang belum memenuhi standar keilmuan. Dengan pendekatan filosofis, sosio-antropolinguistik berbasis data situs nu.or.id, dan analisis wacana ditemukan, bahwa dalam konsep Islam Nusantara menggunakan delapan pendekatan, yang memposisikan Islam memengaruhi budaya Indonesia dan keberhasilannya dalam berdialog dengan budaya Indonesia.Â Kata kunci: Islam, nusantara, budaya, Indonesia, nilai.